Fluorescent Protein Aided Insights on Plastids and their Extensions: A Critical Appraisal - Delfosse, Kathleen; Wozny, Michael R.; Jaipargas, Erica-Ashley; Barton, Kiah A.; Anderson, Cole; Mathur, Jaideep (Frontiers in Plant Science, 2016)
Multi-coloured fluorescent proteins targeted to plastids have provided new insights on the dynamic behaviour of these organelles and their interactions with other cytoplasmic components and compartments. Sub-plastidic components such as thylakoids, stroma, the inner and outer membranes of the plastid envelope, nucleoids, plastoglobuli and starch grains have been efficiently highlighted in living plant cells. In addition, stroma filled membrane extensions called stromules have drawn attention to the dynamic nature of the plastid and its interactions with the rest of the cell. Use of dual and triple fluorescent protein combinations has begun to reveal plastid interactions with mitochondria, the nucleus, the endoplasmic reticulum and F-actin and suggests integral roles of plastids in retrograde signalling, cell to cell communication as well as plant-pathogen interactions. While the rapid advances and insights achieved through fluorescent protein based research on plastids are commendable it is necessary to endorse meaningful observations but subject others to closer scrutiny. Here, in order to develop a better and more comprehensive understanding of plastids and their extensions we provide a critical appraisal of recent information that has been acquired using targeted fluorescent protein probes.